Effect of Hydrolysis and Amount of Yeast on Banana Peel Fermentation into Bioethanol - Luthfi Kurnia Dewi; Chandrawati Cahyani; Adriatic Fitri Rahmadhina; Alexander Tyopannus Prasetya; Meilya Suzan Triyastuti (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Recently, renewable energy sources are needed to meet human energy needs, one of which is bioethanol. Bioethanol can be made from banana peels. Banana peel contains starch which has the potential to be converted into bioethanol through fermentation. There are factors that affect fermentation including the number of microorganisms and glucose levels. One method to increase glucose levels is hydrolysis. The purpose of this study was to determine the effect of hydrolysis and the amount of yeast on bioethanol levels in banana peel fermentation. The research variables used were hydrolyzed and non-hydrolyzed banana peel substrates, as well as variations in the amount of yeast as much as 3 grams; 4.5 grams; and 6 grams. From this research, it was found that hydrolysis causes an increase in glucose levels in the substrate due to the conversion of starch to glucose. Increased glucose levels can affect the yield of bioethanol. The bioethanol content of the hydrolyzed substrate fermentation is 9%-9.5% greater than the bioethanol content of the non-hydrolyzed substrate fermentation of 3%-3.5%. The difference in the amount of yeast used in banana peel fermentation has an effect on the bioethanol content but not significantly enough because the amount of yeast will depend on the glucose content in the substrate.